Class, Culture and Social Change - Kirk, J. author. aut Link
VI, 232 p.
Keywords: Drawing on the work of Raymond Williams, Valentin Volosinov and Mikhail Bakhtin, the book examines key issues for working-class studies including: the idea of the 'death' of class; the importance of working-class writing; the significance of place and space for understanding working-class identity; and the centrality of work in working-class lives.